Grain Sorghum Cost-Return Budget in South Central Kansas - O'Brien, Daniel M.; Shoup, Douglas; Dhuyvetter, Kevin C. (My University, 2014)
This publication projects a budget that reflects expected income and costs based on grain sorghum production in south central Kansas.
MF575_2014_02
Keywords: MF575; Economics; Crops; MF